Effect of cyclosporin A on alveolar bone homeostasis in a rat periodontitis model - Nassar, C. A.; Nassar, P. O.; Rached, RSGA; Holzhausen, M.; Marcantonio, E.; Spolidório, Luis Carlos [UNESP] (Blackwell Munksgaard, 2004)
Objectives: the administration of cyclosporin A has been associated with significant bone loss and increased bone remodeling. The present investigation was designed to evaluate the effects of cyclosporin A on alveolar bone of rats subjected to experimental periodontitis, using serum, stereometric and radiographic analysis.Methods: Twenty-four rats were divided into one of the following groups with six animals each: group I, control rats; group II, in which the animals received a cotton ligature around the lower first molars; group III, in which the rats received a cotton ligature around the lower first molars and were treated with 10 mg/(kg body weight day) of cyclosporin A; group IV, in which the rats were treated with 10 mg/(kg body weight day) of cyclosporin A. At the end of experimental period, at 30 days, animals were killed and the serum calcium and alkaline phosphatase levels were measured in all groups. The distance from the alveolar bone crest to the cemento-enamel junction was measured radiographically for each mesial surface of the lower first molars of each rat. After histological processing, the stereological parameters: volume densities of multinucleated osteoclasts (V-o), alveolar bone (V-b), marrow (V-m), and relation of eroded surface/bone surface (Es/Bs) were assessed at the mesial region of the alveolar bone.Results: Significant decreases in serum calcium were observed in those groups that received cyclosporin A therapy. No significant changes in serum alkaline phosphatase were observed. The therapy with cyclosporin A combined with the ligature placement decreased the V-b and increased the V-o, V-m and Es/Bs at the mesial surface of lower first molars. on the other hand, the radiographic data showed that cyclosporin A therapy diminished the alveolar bone loss at the mesial surface of the lower first molars.Conclusions: Therefore, within the limits of this study, we suggest that cyclosporin A at immunosuppressive levels can bring about an imbalance in the alveolar bone homeostasis in rats. However, in the presence of inflammatory stimulation, the inhibition of the immune system by cyclosporin A may decrease the initial periodontal breakdown.
Keywords: alveolar bone; animal studies; bone loss; etiology; cyclosporin A/adverse effects; digital radiography